Enhancing Biomass and Lipid Production in Messastrum gracile Using Inorganic Carbon Substrates and Alternative Solvents for Lipid Extraction - Pan-utai, Wanida; Pornpukdeewattana, Soisuda; Inrung, Wilasinee; Thurakit, Theera; Srinophakun, Penjit (My University, 2025)
Microalgae show promise as a biomass and bioproduct for applications in various industries. The cultivation of microalgae plays a crucial role in optimizing biomass yield and bioproduct accumulation. The provision of inorganic carbon substrates substantially enhances microalgal growth and lipid biosynthesis, resulting in marked increases in the production of biofuels and other bioproducts. This study examined biomass and lipid accumulation in Messastrum gracile IFRPD 1061 under inorganic stress conditions, previously unreported. M. gracile IFRPD 1061 was subjected to varying conditions of inorganic carbon substrates, 1–3 g·L−1 sodium carbonate and bicarbonate concentration, to enhance biomass and lipid accumulation. Optimal productivity levels were observed with sodium bicarbonate addition of 3 g·L−1 and 1 g·L−1 for biomass and lipids, resulting in productivities of 392.64 and 53.57 mg·L−1·d−1, respectively. Results underlined the effectiveness of sodium carbonate and bicarbonate as inorganic carbon sources for stimulating microalgal growth and enhancing the production of high-value products. The extraction of lipids from freeze-dried biomass of M. gracile IFRPD 1061 demonstrated optimal yield using methanol/hexane solvents compared with the control experiments. Lipid extraction yields using methanol/hexane were 42.18% and 46.81% from oven-dried and freeze-dried biomass, respectively. Lipids extracted from oven-dried M. gracile IFRPD 1061 using methanol/hexane/chloroform solvents indicated the potential of methanol/hexane as a solvent for lipid extraction from dry microalgal biomass using an ultrasonic-assisted technique. This study contributes valuable insights into maximizing biofuel and bioproduct production from microalgae, highlighting A. gracilis as a promising candidate for industrial applications.
Keywords: biomass; extraction; lipid; microalgal growth; productivity